Peran Celebrity Endorsement Dan Citra Merek Dalam Pengambilan Keputusan Pembelian Produk Kosmetik - Shafira Nur Laily; Retno Hidayati (Faculty of Economics and Business Diponegoro University, 2025)
The recent rapid development in the beauty industry has had a significant impack on producers and businesses in this sector. The increasingly fierce competition encourages local producers in Indonesia to create new brands that are able to compete with other leading brands. Wardah has become on of the altenative beauty product choices for consumers. However, there are still many consumers who are confused in making purchasing decisions about Wardah product. Seeing these conditions, this study aims to analyze celebrity endorsement and brand image on purchasing decision making with self-congruity as an intervening variable for Wardah consumers in Semarang. This stufy uses the self-congruity theory approach as the basis for research. In addition, there are inconsistencies in the results of previous research which is the reason this research was conducted.The population used in this study were Wardah consumers who live in Semarang, are at least 17 years old and who have purchased Wardah products at least once in the last 6 months. The number of samples used in this study were 150 respondents. The method of data collection is done through a questionnaire. The data obtained were then processed and analyzed using the Structure Equation Modeling (SEM) analysis techniques with AMOS 24 analysis tools.The results of this study indicate that self-congruity and celebrity endorsement have a positive and significant effect on purchasing decision making. Celebrity endorsement and brand image have a positive and significant effect on self-congruity. As well as the rejection of the effect of brand image on purchasing decision making and the mediating role of self-congruity in the relationship between celebrity endorsement and brand image and purchasing decision making. Based on these result, it leads to the conclusion that purchasing decision making can be improved through celebrity endorsement and self-congruity. This research also has managerial implications and recommendations for future research.